2021
DOI: 10.3390/ijms22094630
|View full text |Cite
|
Sign up to set email alerts
|

The Implication of Reticulons (RTNs) in Neurodegenerative Diseases: From Molecular Mechanisms to Potential Diagnostic and Therapeutic Approaches

Abstract: Reticulons (RTNs) are crucial regulatory factors in the central nervous system (CNS) as well as immune system and play pleiotropic functions. In CNS, RTNs are transmembrane proteins mediating neuroanatomical plasticity and functional recovery after central nervous system injury or diseases. Moreover, RTNs, particularly RTN4 and RTN3, are involved in neurodegeneration and neuroinflammation processes. The crucial role of RTNs in the development of several neurodegenerative diseases, including Alzheimer’s disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 118 publications
0
6
0
Order By: Relevance
“…Given Rtn4’s shared characteristics with other known ER membrane-curving proteins (Zurek et al, 2011; Voeltz et al, 2006; Shibata et al, 2008; Hu et al, 2008), it is reasonable to think that this model could be generalized to other reticulons and the REEPs/DP1/Yop1p family of proteins. Additionally, considering the many links between ER structure and disease (Sharoar et al, 2016; Parlakgül et al, 2022), some implicating Rtn4 directly (Zheng et al, 2022; Zhang et al, 2021; Kulczyńska-Przybik et al, 2021b; Boghdadi et al, 2018; Kulczyńska-Przybik et al, 2021a; Chiurchiù et al, 2014), the results of this study may provide additional insight in this regard.…”
Section: Discussionmentioning
confidence: 92%
“…Given Rtn4’s shared characteristics with other known ER membrane-curving proteins (Zurek et al, 2011; Voeltz et al, 2006; Shibata et al, 2008; Hu et al, 2008), it is reasonable to think that this model could be generalized to other reticulons and the REEPs/DP1/Yop1p family of proteins. Additionally, considering the many links between ER structure and disease (Sharoar et al, 2016; Parlakgül et al, 2022), some implicating Rtn4 directly (Zheng et al, 2022; Zhang et al, 2021; Kulczyńska-Przybik et al, 2021b; Boghdadi et al, 2018; Kulczyńska-Przybik et al, 2021a; Chiurchiù et al, 2014), the results of this study may provide additional insight in this regard.…”
Section: Discussionmentioning
confidence: 92%
“…Its function is mainly implicated in DNA binding or epigenetic modification, neuronal differentiation, and neurodegenerative diseases such as AD ( Recabarren and Alarcon, 2017 ). Considerable evidence suggests that all RTN proteins and receptor NgR are engaged in the pathology change of AD by regulating the beta-site amyloid precursor protein-cleaving enzyme 1 (BACE1) function or APP processing, and thereby product amyloid β in the brain ( Kulczynska-Przybik et al, 2021 ). Previous studies have observed a significant decrease in RTN1 expression in the frontal cortex of AD patients ( Kim et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, glia and T cells, especially M2 macrophages/microglia, and T helper (Th) 2 cells and regulatory T (Treg) cells have protective roles in maintaining motor neuron viability. At a later stage, cytotoxic M1 macrophages/microglia and proinflammatory Th1 and Th17 T cells become more active [ 164 , 165 , 166 , 167 , 168 ].…”
Section: Therapeutic Strategies For Als Targetsmentioning
confidence: 99%